Multi-Agent Technologies and Machine Learning - Sheremet, Igor A. (Artificial Intelligence, 2023)
This book discusses multi-agent technologies (MATs) and machine learning (ML). These tools can be integrated and applied in industry, commerce, energy, medicine, psychology, and other areas. This volume consists of six chapters in three sections that discuss the integration, applications, and advanced results of MATs and ML.